2010
DOI: 10.3354/ab00275
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive cycle and biochemical composition of Hexaplex trunculus (Gastropoda: Muricidae) from Bizerte lagoon, northern Tunisia

Abstract: This study investigates the reproductive cycle, size at first sexual maturity and biochemical composition of Hexaplex trunculus from the Bizerte lagoon (northern Tunisia). Overall, females predominated over males, resulting in an unbalanced sex ratio of 1.2:1. Males dominated in the smaller size classes (< 40 mm shell length, SL), sex ratios were balanced at the 40 to 50 mm SL range, and females dominated in the larger size classes (> 50 mm SL). The gonad developmental stages and the gonadosomatic index (GSI) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 47 publications
2
19
1
6
Order By: Relevance
“…This finding agrees with other studies conducted on this species along the Catalan coast (northeastern Spain) (Ramón & Amor, 2001 and in the Ria Formosa lagoon (southern Portugal) , being also commonly observed in another muricid gastropod (the banded murex, Hexaplex trunculus) caught along the Tunisian coast (e.g. Elhasni et al, 2010;Gharsallah et al, 2010). In the present study, female-biased sex ratios occurred mainly between April and August, but with a clear period of highly unbalanced sex ratios from April to June, coinciding with the breeding and spawning season of B. brandaris locally.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding agrees with other studies conducted on this species along the Catalan coast (northeastern Spain) (Ramón & Amor, 2001 and in the Ria Formosa lagoon (southern Portugal) , being also commonly observed in another muricid gastropod (the banded murex, Hexaplex trunculus) caught along the Tunisian coast (e.g. Elhasni et al, 2010;Gharsallah et al, 2010). In the present study, female-biased sex ratios occurred mainly between April and August, but with a clear period of highly unbalanced sex ratios from April to June, coinciding with the breeding and spawning season of B. brandaris locally.…”
Section: Discussionsupporting
confidence: 82%
“…Indeed, if during bottom trawling a breeding aggregation is caught by the trawl path, most likely females will predominate in the catches and generate strongly female-biased sex ratios. A similar predominance of females over males also occurred during the breeding and spawning season of H. trunculus in Tunisian waters (Elhasni et al, 2010;Gharsallah et al, 2010). In the present study, while sex ratios were balanced in the smallest size classes (< 50 mm SL), the proportion of females in the samples augmented by increasing specimen size, generating female-biased sex ratios in the largest size-classes (> 50 mm SL).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In fact, Lahbib et al (2009) registered only one period in both sexes between January and May-June. Gharsallah et al (2010) reported that in both sexes of H. trunculus, gamete release occurred mainly from March to May (with a spawning peak between March and April), followed by a period of empty gonads between June and August. Moreover, another study on the reproductive cycle of H. trunculus from the Gulf of Gabès detected just one period of gametic emission in both sexes (January-May for males and April-May for females) (Elhasni et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies focusing on H. trunculus have been based on sexual abnormality known as imposex and reproductive biology (e.g., Axiak et al, 1995;Gharsallah et al, 2010;Terlizzi et al, 1998;Lahbib et al, 2008;Lahbib et al, 2010). Nevertheless, the knowledge of fishing effort and stock structure of this species, which occurs in a large distribution range with different environmental conditions, is still very limited.…”
Section: Introductionmentioning
confidence: 99%